Boos : An android application on learning KadazanDusun for non-native KadazanDusun speakers - Marius, E.; Jupit,, A. J. R. (2021)
Language learning using mobile application become a revolution for a learning platform as more people nowadays turns to smartphone and tablet. As there are numerous language learning mobile apps that have been developed, it indicates that language can now be learned by all people from different backgrounds and ages. Hence, an Android application on learning KadazanDusun language is introduced as a learning platform to respond to the new technology since there is no KadazanDusun learning platform using Android technology that provided for non-native KadazanDusun speakers. Boos as the name of the language learning application has developed to aid the learners to learn KadazanDusun language in interactive way. This application would be useful and provides effective learning to the learner.